Temperature-Dependent Raman Scattering and Correlative Investigation of AlN Crystals Prepared Using a Physical Vapor Transport (PVT) Method - Zhe Chuan Feng; Manika Tun Nafisa; Yao Liu; Li Zhang; Yingming Wang; Xiaorong Xia; Ze Tao; Chuanwei Zhang; Jeffrey Yiin; Benjamin Klein; Ian Ferguson (Photonics)
Ultrawide bandgap (UWBG) AlN c- and m-face crystals have been prepared using the physical vapor transport (PVT) method and studied penetratively using temperature-dependent (TD) Raman scattering (RS) measurements under both visible (457 nm) and DUV (266 nm) excitations in 80–870 K, plus correlative atomic force microscopy (AFM) and variable-angle (VA) spectroscopic ellipsometry (SE). VASE identified their band gap energy as 6.2 eV, indicating excellent AlN characteristics and revealing Urbach energy levels of about 85 meV. Raman analyses revealed the residual tensile stress. TDRS shows that the E2(high) phonon lifetime decayed gradually in the 80–600 K range. Temperature has the greater influence on the stress of m-face grown AlN crystal. The influence of low temperature on the E2(high) phonon lifetime of m-plane AlN crystal is greater than that of the high-temperature region. By way of the LO-phonon and plasma coupling (LOPC), simulations of A1(LO) modes and carrier concentrations along different faces and depths in AlN crystals are determined. These unique and significant findings provide useful references for the AlN crystal growth and deepen our understanding on the UWBG AlN materials.